Vigilance and strategic role in improving the level of nursing services / Applied Research in Ghazi al-Hariri Hospital - داود فضيلة سلمان; ابراهيم حسين علي (Journal of Economics and Administrative Sciences, 2017)
The current research aims to focus on strategic vigilance dimensions and contained (environmental vigilance, technological vigilance, competitive vigilance, vigilance marketing) to improve nursing services, which include a) the quality, timeliness, problem-solving and decision-making, relationships with others, leadership skills) and measure the degree link and influence between strategic vigilance in the hospital respondent and improve nursing service that the problem of the research lies in the weakness of strategic plans and health organizations in general and the hospital surveyed (martyr Ghazi al-Hariri), in particular, the lack of awareness of the hospital researched strategy vigilant management to improve nursing services, from this standpoint, the researcher shed light on this problem, trying to develop the concept of strategic vigilance and improvement of nursing services provided at the martyr Ghazi al-Hariri in order to raise the level of services provided in the hospital under study, as the researcher tested the correlation and impact between research variables, which have been measured on a sample search of Palmlakat Hospital nursing worker martyr Ghazi al-Hariri of the health department of the Medical city.